Regorafenib outcomes from the population based South Australian Metastatic Colorectal Cancer Registry. Issue 4 (23rd November 2021) - Alawawdeh, Anas; Price, Timothy; Karapetis, Christos; Piantadosi, Cynthia; Padbury, Rob; Roy, Amitesh; Maddern, Guy; Moore, James; Carruthers, Scott; Roder, David; Townsend, Amanda R.
Abstract: Aim: Reviewing outcomes of regorafenib use in metastatic colorectal cancer using real‐world data from the South Australian Metastatic Colorectal Cancer Registry. Methods: A retrospective review of the characteristics and outcomes of patients who received regorafenib in the Registry up to December 2018. The registry started in February 2006. Results: Fifty‐three patients received regorafenib therapy since approved by the therapeutic goods administration in November 2013. The median age was 66 (range 34–82). 66% were male, 66% had stage IV disease at diagnosis, 53% had liver only involvement, whereas 13% had liver and lung disease and 6% had lung only involvement. 75% had left‐sided primary. KRAS was available in 35/53 patients with 49% of them being WT. BRAF status was known in 8/53 with 25% of them having a mutated variant. MSI testing was known in 14 patients in whom 21% of them had MSI‐High tumors. Prior lines of treatment received: one line 4%, two 9%, three 23%, four 26%, >four 37%. Prior biological use: bevacizumab 72%, anti‐EGFR 100% (for RAS WT). Median survival from diagnosis was 3.3 years (95% CI, 2.8–3.8 years). Median survival from the start of regorafenib was 7.1 months (95% CI, 4.8–9.4 months) and the 12‐month survival rate was 28%. Conclusion: The survival outcome for those patients from our population‐based registry who access regorafenib is in keeping with reports from large, randomized trials. Thus, clinicians can quote local real world data when discussing efficacy and access to regorafenib therapy for mCRC patients. Abstract : This is a retrospective review of patients from the South Australian Metastatic Colorectal Cancer Registry who received Regorafenib. Results showed similar survival outcomes when compared with large randomized trials which provides guidance for oncologists when discussing efficacy and access to regorafenib therapy.